3D modeling of complex spatial forms by cognitive programming technology method - Sokol, G. V.; Lytovchenko, А. P.; Kirakosyan, A. A.; Shut, V. V.; Shugailo, A. O. (Sp. z o.o. "Nauka i studia", 2020)
This article examines the problem of harmonization of 3D modeling and 3D prototyping of complex spatial forms within the framework of cognitive programming technology. The ways of its solution is offer on the example of the 3D Studio MAX environment. An analysis of the strategic trend of the development of digital programmable technology, from the mathematical modeling of physical, biological and other natural processes when the production-element basis of the nano-level has been reached, has led to the creation of a technology for the direct reproduction of three-dimensional spatial objects of complex forms. Informatics is not only an ontology of projects, but also its spatial materialization. Biological objects are artificially reproduced based on cognitive programming technology. Now in the world in all areas of knowledge there is a burst of digital modeling: through computer engineering and digital modeling is practically any new product. At Japanese exhibitions, a demonstration of the bulk copy process is already underway: digital input of objects is performed at the input, then processing in the 3D modeling environment - and as a result you can print a copy of the prototype. A printer that prints parts for itself, an electric battery with a variable battery, gadgets communicate with each other and are responsible for the comfort of the owner - the reality of the new digital world, which is formed now. With regard to the programmable technology of info communication, not the bandwidth of the channel, but the transformation of the properties of the communication of physical nature in the properties of biological nature and social needs is important.
Keywords: 3D modeling; sculpting; fast prototyping; cognitive programming technology; 3D prototyping; strategic trend; complex spatial forms